Pregnancy outcome study between Pradhan mantri surakshit matriva abhiyan service utilization group and pradhan mantri surakshit matriva abhiyan service non-utilization group: a comparative study - Mandal, Purnima; Mandal, Jaydeb (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Safe pregnancy has become a social movement in our country. Almost 15 % of all pregnant women can develop potentially life-threatening complications. As a result, identification of high-risk pregnancies at earliest stage will be useful in directing appropriate intervention. Hence this study was done to evaluate the betterment of pregnancy outcome of the women who had taken the adequate service of Pradhan Mantri Surakshit Matriva Abhijyan service (PMSMA) than who had not. Method: A longitudinal study was conducted at Malda medical college during January 2019 to June 2019. 385 women selected who had taken at least three antenatal checkups (from record analysis) at PMSMA designated clinic and another 385 women selected who had not taken PMSMA services. Women of both groups were followed up their delivery events and puerperal days till discharge from hospital. Pregnancy outcomes were compared and statistical analysis of both groups were done by SSPS software. Results: A significant outcome difference of PMSMA service utilized and non-utilized groups in respect to fetal and maternal parameters including moderate to severe anemia, (12.98% vs 26.49%), intra uterine growth retardation (IUGR, 20.0% vs 29.87%), hypertensive disorders in pregnancy (HDP, 8.31% vs 13.50%), low-birth-weight (21.30% vs 31.16%) and stillborn (1.29% vs 2.89%) were observed. Conclusions: This study showed positive pregnancy outcome of PMSMA utilized group than non-utilized group. Improving the availability and accessibility of quality antenatal and delivery care through PMSMA services in all our institutions, will improve pregnancy outcome.